Pengaruh Kualitas Pelayanan Kesehatan terhadap Kepuasan Pasien Penerima Bantuan Iuran di Puskesmas Pahandut Kota Palangka Raya - Rolly Adinovi; Rinto Alexandro (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2021)
The purpose of this study is to analyze the significance of the effect of service quality dimensions including reliability, responsiveness, assurance, empathy, tangibles to the level of poor people's health insurance patient satisfaction in Public Health Center of Pahandut Palangkaraya City. Based on the analysis of overall service gap dimensions, the fit between the services provided by health centers in the hope of Palangkaraya Pahandut community insurence patients there is a gap / level of satisfaction (- 10:54), these scores were categorized in groups, although not yet fully meet the expectations of patients community insurence, but service provided is good enough. Based on the results of the regression analysis above we can conclude that all the variables of service quality dimensions (Reliability, Responsiveness, Assurance, Empathy, Tangible) jointly have a significant positive effect on patient satisfaction and Public Health Center of Pahandut Palangka raya City. These results indicate that the alternative hypothesis (Ha) can be accepted and the hypothesis zero (Ho) is rejected. While the major effect is variable Assurance (1052), Reliability (1004), Tangible (1039), Responsiveness (1714), Empathy (1029) on patient satisfaction community insurence. The next is the R ² value of (0456) showed that 45.6% of patient satisfaction variables can be explained by service quality are Reliability, Responsiveness, Assurance, Empathy, and the remaining 54.4% Tangible while others described the other variables that are not included in this study model . Then, based on gap analysis (a match between expectations of the performance) of each dimension, are as follows, Responsiveness variable (-0.78) score was categorized as moderate. then followed the next variable Tangible variable (-0.88), variable Reliability (-0.57), assurance variable (-0.11), Empathy and the latter variable (-0.11). Although not yet fully provided the service as expected but the district Public Health Center of Pahandut Palangka raya City good enough but should be improved.